Bridging the Communication Gap Using DISC Theory of Leadership in the Hybrid Work Environment - Dr. Jyoti Doley; Dr. Meenakshi Dey (International Journal of Engineering and Management Research, 2021)
The recent changes in work environment owing to the COVID 19 pandemic has made us rethink the utility of office space at a time when an exponential growth in the use of online platforms has been observed. With the flexibility of working space and timing, employees and the organizational heads have redefined work culture and the old adage of strict 9 to 5 job seems to have been completed changed. The current paper attempts to understand the four behavioral patterns of DISC exhibited by leaders in any work environment. It explains what are the four behavioral traits and how they influence communication. And in a hybrid work environment, with lot of flexibility in time and space, what steps are to be taken in order to make communication effective and avert miscommunication as half of the employees work offline while the other half works online.